Production Plant Redistribution and Scheduling: an Integrated Approach - Jaramillo, Daniel; Uriarte, Juliana; Cardona, Luis Felipe (Ingeniería Solidaria, 2014)
The main concern of companies when carrying out a plant redistribution project is the interruption of manufacturing operations while departments are transferred. This article presents an optimization model for scheduling the transference of departments and production, in order to guarantee fulfillment of demand during a plant redistribution project execution. For this purpose, a mixed complete linear programming model (pem from its Spanish acronym) was applied that minimizes the cost of transferring departments, ensures demand fulfillment and limits the duration of the project to an established maximum. The results show that, when average plant machinery use is greater than 60%, the redistribution project and production scheduling are interdependent, thus the need for an integrated approach such as the one proposed in this article. This is derived from the research project “Optimization of Plant Redistribution Processes in Flexible Manufacturing” (“Optimización de procesos de redistribución de planta en manufactura flexible”) carried out at the Universidad Icesi in 2013-2014.
Keywords: plant distribution; plant redistribution; optimization; project scheduling